Measuring Public Trust in Military Engagement during Civil Emergencies: Insights from Disaster-Prone Communities in Indonesia - Banjarnahor, Joshua; Joanna, Charvet; Crosbie, Kho (Civil and Military Cooperation Journal, 2026)
Public trust plays a critical role in shaping the effectiveness of civil emergency response, particularly in contexts where military actors are actively involved. In disaster-prone countries such as Indonesia, the military serves as a key operational force in emergency management, yet its involvement raises important questions regarding legitimacy, accountability, and public perception. This study examines the determinants and dynamics of public trust in military engagement during civil emergencies. Employing a mixed qualitative approach that integrates a systematic literature review with contextual analysis of disaster-prone regions in Indonesia, this research develops a conceptual framework linking trust, institutional legitimacy, and civil-military coordination. The findings indicate that public trust is shaped by perceived effectiveness, transparency, community engagement, and alignment with humanitarian values. While military involvement enhances operational efficiency, trust remains contingent upon the balance between authority and accountability. The study contributes to the literature by offering an integrative framework for understanding public trust in civil-military contexts and provides policy-relevant insights for strengthening disaster governance in high-risk environments.